Impacts of Health Reform Plan in Iran on Health Payments Distributions and Catastrophic Expenditure - Morteza JOSHANI KHEIBARI; Reza ESMAEILI; Mahmood KAZEMIAN (Tehran University of Medical Sciences, 2019)
Background: Health reform in Iran began in 2014, aimed at improving financing pattern of health services. We assessed the reform by changes in variables representing distribution of health payments and catastrophic expenditures. Methods: Using data from households' income-expenditure survey, this study computed the financial variables, representing poverty line and households at poor state, household's catastrophic health expenditure, fairness in financial contribution (FFC) index, and household's impoverishment state, in the years 2010-2016, in urban and rural areas. The variables were computed by special software designed for this study, based on C-Sharp(C#) programming language, with yearly data on more than 38000 households, each with 1072 information sources. Results: The food share-based poverty line after sharp rise in 2010-2013, in 2014-2016 raised slowly, and the average percent of households facing catastrophic health expenditure, after sharp rise in 2011-2013, left at 3.25 in 2014-2015 and raised to 3.45 in 2016. The average FFC index remained at 0.839 to 0.837 in 2013-2016. However, interestingly, the average percent of households impoverished after out-of-pocket payments improved from 1.36 to 0.912 in 2013-2016. Conclusion: In three years of health reform, the major impact of reform was considerable improvements in the rate of the impoverished after out-of-pocket payments. The reform had limited impacts on the rates of households facing catastrophic health expenditure, and on FFC indexes, for the rural and urban residents.